A proposed approach for quantitative benefit‐risk assessment in diagnostic radiology guideline development: the American College of Radiology Appropriateness Criteria Example. Issue 1 (19th October 2016) - Agapova, Maria; Bresnahan, Brian B.; Higashi, Mitchell; Kessler, Larry; Garrison, Louis P.; Devine, Beth
Abstract: The American College of Radiology develops evidence‐based practice guidelines to aid appropriate utilization of radiological procedures. Panel members use expert opinion to weight trade‐offs and consensus methods to rate appropriateness of imaging tests. These ratings include an equivocal range, assigned when there is disagreement about a technology's appropriateness and the evidence base is weak or for special circumstances. It is not clear how expert consensus merges with the evidence base to arrive at an equivocal rating. Quantitative benefit‐risk assessment (QBRA) methods may assist decision makers in this capacity. However, many methods exist and it is not clear which methods are best suited for this application. We perform a critical appraisal of QBRA methods and propose several steps that may aid in making transparent areas of weak evidence and barriers to consensus in guideline development. We identify QBRA methods with potential to facilitate decision making in guideline development and build a decision aid for selecting among these methods. This study identified 2 families of QBRA methods suited to guideline development when expert opinion is expected to contribute substantially to decision making. Key steps to deciding among QBRA methods involve identifying specific benefit‐risk criteria and developing a state‐of‐evidence matrix. For equivocal ratings assigned for reasons other than disagreement or weak evidence base, QBRA may not be needed. In the presence of disagreement but the absence of a weak evidence base, multicriteria decision analysis approaches are recommended; and in the presence of weak evidence base and the absence of disagreement, incremental net health benefit alone or combined with multicriteria decision analysis is recommended. Our critical appraisal further extends investigation of the strengths and limitations of select QBRA methods in facilitating diagnostic radiology clinical guideline development. The process of using the decision aid exposes and makes transparent areas of weak evidence and barriers to consensus.